Psychoanalysis, Corporeality and Haptics in Covid-19 Times - Arka Chattopadhyay (EJP import test, 2021)
Summary: The article examines the haptic dimension of the relation between the Subject and the Other. It speculates about the complex affective dynamic in the wake of Covid-19 (especially the first wave in 2020) that hovers between fear and anxiety as the scansion of a broken ‘social bond’ of inter-subjectivity. From Lacan and Anzieu, I build psychoanalytic notions of the skin and the touch that hold on to the slip-bridge between the unconscious subject and the Other. This Other is not asocial and as the article argues, the status of the Other undergoes notional shifts from the animate to the inanimate and assumes political implications for social hierarchies. We engage with the phenomenology of touch that drives the Indian caste system to connect this dialectic of tactility (despite the gradual consensus about aerosol infections) with the Coronavirus situation and see how it inflects contemporary caste-practices in India. As we shall see, the Covid feeling of whether to touch or not touch the inter-class and inter-caste social Other, changes ideas of purity and impurity and modifies the status of the intermediate object that carries infection as a possibility.
Keywords: Caste; Covid 19; Haptics; Psychoanalysis; skin